Inhibitory Effects of Chalcone on the Replication of Poliovirus in Vitro (Baghdad Science Journal, 2013)
The compound chalcon originally is extracted form some plant and herbs, the studies of the antiviral activity of this compound were done in two cell line cultures the L2OB and RD, the compound relatively non toxic to both cell lines of the concentration of 32?g/ml or less ,the compound have significantly anti poliovirus activity in both L2OB cell line and RD cell line, we find that the concentration of 0.03 ?g/ml or more inhibit the 100TCDID50 of the poliovirus .The therapeutic index(TI)used in this study to evaluate the drug activity ,( TI is the ratio of dose of drug which is just toxic to the cells to the does which is just inhibit the viral multiplication, if this index more than one the margin of safety of drug is according great ) .In this study the TI of chalcone against poliovirus is 266,therefore this compound if used in man have little or no side effect.